Mengurai Makna Pelayanan Mukjizat Paulus Menurut Kisah Para Rasul 20:1-12 Dari Bingkai Kaum Pentakostal - Kosma Manurung (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
The Apostle Paul is a very important theologian in the New Testament who has also set an example for believers in many generations in terms of faith, ministry, and daily life. This article intends to analyze the meaning of the apostle Paul's miraculous ministry in Acts 20:1- 12 from the perspective of the Pentecostals. By using a qualitative descriptive method and supported by literature review, it is hoped that it will be able to explain in a careful, in-depth, and academically strong manner related to the Bible's account of the story of Paul's ministry, the description of Paul's ministry in Acts 20:1-12, as well as the meaning of the Pentecostals for the story in this passage. In conclusion, Pentecostals interpret the story of the apostle Paul's miraculous ministry as the importance of having an encounter with God, the importance of discipleship, perseverance in serving God, and the manifestation of God's power that accompanies the ministry of believers.